2001
DOI: 10.1161/hs0901.095639
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of High-Density Lipoprotein Cholesterol Are Associated With Echolucent Carotid Artery Plaques

Abstract: Background and Purpose-Ultrasound-assessed plaque morphology is an independent predictor of ischemic stroke. The purpose of this population-based cross-sectional nested case-control study was to examine the risk factors associated with carotid plaque morphology. Methods-Ultrasonography of the right carotid artery was conducted on 6727 participants in a population health survey (response rate 79%). Plaque echogenicity, defined as reflectance of the emitted ultrasound signal, was scored as echolucent, predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 47 publications
4
66
1
Order By: Relevance
“…10,29,30 Although there is no strong evidence at present that supports the selection of patients for treatment based on sonography examination, it has been suggested that measurement of echolucency together with degree of stenosis may improve the selection of patients for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,29,30 Although there is no strong evidence at present that supports the selection of patients for treatment based on sonography examination, it has been suggested that measurement of echolucency together with degree of stenosis may improve the selection of patients for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent literature, the plaque morphology was classified into 4 grades. [10][11][12] Grades 1 and 2 were considered as high-risk plaque morphology; grade 3 was medium risk and grade 4 was low risk of stroke. All of the patients with a high-risk plaque were treated if stenosis was more than 50%.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology of plaque was assessed by US; the plaque morphology was classified into 4 grades [13][14][15] : Grades 1 and 2 were considered high-risk-morphology plaque, grade 3 was medium risk, and grade 4 was low risk of stroke. All patients with a high-risk-morphology plaque were treated if stenosis was Ͼ50%.…”
Section: Preprocedural Evaluationmentioning
confidence: 99%
“…All subjects aged 55 to 74 years, random 5% samples of subjects in other age groups up to age 84 years, as well as 308 men aged 40 to 54 years (selected on the basis of high total cholesterol and/or low high density lipoprotein cholesterol) were invited to a second visit for more extensive examinations. A total of 6891 subjects (3393 men) attended the second visit, representing 79% of the eligible population (11). Serum samples were drawn for future analysis of sex hormones in a random sample of 1605 men, and echocardiography was performed in 1316 of them.…”
Section: Study Populationmentioning
confidence: 99%